The evaluation of immigration policies - Ulf Rinne (Institute for the Study of Labor (IZA), 2012)
This chapter summarizes the literature on the evaluation of immigration policies. It brings together two strands of the literature dealing with the evaluation of labor market programs and with the economic integration of immigrants. Next to immigrant selection and settlement policies, there are four types of interventions that aim at improving the economic and social outcomes of immigrants: a) introduction programs, b) language training, c) labor market programs, and d) anti-discrimination policies. The chapter discusses problems associated with the evaluation of such programs, presents methodological approaches to circumvent these problems, and surveys empirical results and findings. It concludes with lessons from previous research and identifies avenues for future research.
urn:nbn:de:101:1-201206146426
Keywords: J15; J24; J61; J62; 330; migration; program evaluation; immigrant selection; settlement policy; introduction programs; discrimination; language training; active labor market policy; integration; Migrationspolitik; Wirkungsanalyse; Soziale Integration; Berufliche Integration